Draw 50 boats, ships, trucks & trains. - Ames, Lee J. (Doubleday & Company, Inc. Garden City, New York, 1976)
Draw 50 Boats, Ships, Trucks, and Trains teaches aspiring artists how to draw with ease by following simple, step-by-step instructions. Celebrated author Lee J. Ames shows readers how to draw dozens of modes of transportation from throughout history, such as a Viking ship and the Santa Maria, as well as a nuclear submarine, a Jeep, and a tractor-trailer. Ames's illustration style and renowned drawing method has made him a leader in the step-by-step drawing manual, and the 31 books in his Draw 50 series have sold more than three million copies. Ames's instruction allows seasoned artists to refine their technique and guides amateurs to develop their own artistic abilities. Even the youngest artists can make any type of vehicle look great. It's easy to build all kinds of vehicles when it's done the Draw 50 way.
8 - 12 years
Keywords: Art -- Technique; Drawing -- Boats; Drawing -- Ships; Drawing -- Trucks; Drawing -- Trains